2015
DOI: 10.1128/aac.02663-14
|View full text |Cite
|
Sign up to set email alerts
|

Structural Variations of the Cell Wall Precursor Lipid II and Their Influence on Binding and Activity of the Lipoglycopeptide Antibiotic Oritavancin

Abstract: Oritavancin is a semisynthetic derivative of the glycopeptide antibiotic chloroeremomycin with activity against Gram-positive pathogens, including vancomycin-resistant staphylococci and enterococci. Compared to vancomycin, oritavancin is characterized by the presence of two additional residues, a hydrophobic 4=-chlorobiphenyl methyl moiety and a 4-epi-vancosamine substituent, which is also present in chloroeremomycin. Here, we show that oritavancin and its des-N-methylleucyl variant (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 68 publications
(103 reference statements)
2
56
3
Order By: Relevance
“…These effects are also related to the capacity of oritavancin to specifically bind to lipid II, with additional interaction sites compared with its precursor chloreremomycin, which can explain its improved activity on vancomycin-resistant strains [37]. Solid-state nuclear magnetic resonance (NMR) studies have indeed shown that oritavancin possesses two binding sites on the lipid-linked disaccharide-pentapeptide monomers in S. aureus (D-Ala-D-Ala termini, like vancomycin, but also the pentaglycyl bridging segment via its lipophilic side chain on the dissacharide and components of its aglycon structure).…”
Section: Mechanism Of Action Of Lipoglycopeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects are also related to the capacity of oritavancin to specifically bind to lipid II, with additional interaction sites compared with its precursor chloreremomycin, which can explain its improved activity on vancomycin-resistant strains [37]. Solid-state nuclear magnetic resonance (NMR) studies have indeed shown that oritavancin possesses two binding sites on the lipid-linked disaccharide-pentapeptide monomers in S. aureus (D-Ala-D-Ala termini, like vancomycin, but also the pentaglycyl bridging segment via its lipophilic side chain on the dissacharide and components of its aglycon structure).…”
Section: Mechanism Of Action Of Lipoglycopeptidesmentioning
confidence: 99%
“…A large number of studies have examined the in vitro activity of these compounds against [17], which leads, by steric hindrance, to an inhibition of the glycan chain extension and, to a lesser extent, of crosslinking between peptidic stems. Oritavancin has additional interactions with the pentaglycyl bridge and the D-iso-glutamine residue in position 2 of the pentapeptide terminus of lipid II (zone highlighted in orange) [37], which allow it to be a stronger inhibitor of transpeptidases [38] collections of Gram-positive clinical isolates, yet many of these studies were performed using broth that was not supplemented by polysorbate-80, which is needed to prevent the adsorption of the drugs to the plastic [40][41][42]. Table 1 therefore focuses on recent studies that have used the standard procedure currently recommended by the Clinical Laboratory Standards Institute (CLSI), i.e., 0.002 % polysorbate-80 added to the culture medium [43].…”
Section: Spectrum Of Activitymentioning
confidence: 99%
“…The lipoglycopeptides differ from glycopeptides in that they have lipophilic tails attached to the amino sugar, causing increased binding affinity to Lipid II and allowing them to anchor to the bacterial cell membrane. This additional mechanism causes stabilization with Lipid II, allowing them to concentrate at their site of action, increasing their potency and, for oritavancin, causing destabilization of the cell membrane, resulting in loss of membrane potential . Teicoplanin, which was introduced in Europe in 1988, was the first natural agent of this class of antibiotics.…”
Section: Lipoglycopeptidesmentioning
confidence: 99%
“…The first approved antibiotic targeting lipid II was the glycopeptide vancomycin 7 (Scheme 4). Glycopeptide antibiotics are active against a broad variety of Gram-positive pathogens and act by binding to the D-Ala-D-Ala-dipeptide terminus in lipid II on the extracellular membrane surface via several hydrogen bonds and ionic interactions (Jia et al 2013;Münch et al 2015).…”
Section: Lessons Learned From Druggable Targets In Bacteriamentioning
confidence: 99%